Категориальное прогнозирование связного энергопотребления в коммунально-бытовом секторе - Вороненко, Дмитрий Иванович; Махотило, Константин Владимирович (Eastern-European Journal of Enterprise Technologies, 2009)
The task of increase of prediction precision of daily domestic power consumption alteration sign and range is considered. It is suggested to pass from the task of regression to the task of classification . The optimum set of categories is determined. The categorical power consumption predictor based on cascade correlation neural network synthesized.